Implementación del sistema integrado de gestión en las empresas caso específico: área contable y financiera (2016)
An Integrated Management System is considered a management tool that helps increase organizational performance through proper management of its processes, which is reflected in the continuous improvement of these; also in compliance with the strategic objectives and in meeting the needs, interests and expectations of its customers, stakeholders and interest groups. This paper had as its main purpose to analyze whether Colombian companies are aware of the importance of implementing an Integrated Management System in them, focused on the accounting and financial processes, where it has observed a low preparation by managements at the time implementations of this system. In addition, a quantitative and qualitative research was the finding little knowledge of the subject in the academic population of the Universidad de San Buenaventura (teachers and students). Attached to this, a practical guide was built so that entrepreneurs can make the implementation of this System in their accounting departments more effectively, in order to better manage the financial information to prevent fraud, penalties and possible financial failures.